Postural assessment of children with spastic cerebral palsy: a cross-sectional study - Gupta, Aarti; Sen, Siddhartha; Bajpai, Rishabh (International Journal of Research in Medical Sciences, 2023)
Background: Children with cerebral palsy (CP) exhibit gait difficulties, posture alignment issues when standing, and issues with body orientation in space as a result of both primary and secondary CP deficits. The purpose of this study was to analyze the posture of children with spastic diplegic CP. Methods: The 17 subjects of age group 3-10 years with GMFCS scale I-II of CP were taken in the study and compared with age matched control group of 17 typical development (TD) children. The postural assessment was carried out using the photographic method. Angles like the head angle, angle of hip joint, angle of ankle joint were calculated with the help of Matlab script. Results: The Pearson’s correlation was utilised to examine the relationship between various postural angles in the CP group while the t-test was used to analyse differences between the two groups. The two groups were found to differ in every measure but horizontal alignment of acromion (HAAC), angle of hip (AH), angle of knee (AK), angle of ankle (AA), scapular alignment right and left (SAR) (SAL) were significantly different in CP group rather than TD group (p<0.01) and postural angles were found to be significantly correlated in CP group (p<0.01). Conclusions: The postural angles in children with spastic CP are deviated from the normal angle. Correct analysis of posture gives us a tool to identify the altered biomechanics and further design an intervention program which will address the mal-aligned structures.